Coolness Perception on Samsung Smartphone and How It Create Brand Love - Ade Pranata, Lukiawan; Roostika, Ratna (Selekta Manajemen: Jurnal Mahasiswa Bisnis & Manajemen, 2023)
Current technological advancements have changed many of its users’ perspectives in choosing any product, including by considering coolness element. An innovative technology makes manufacturers being more competitive by providing the latest features of technology and giving more prestige to its consumers. Not only have to be attractive, but the coolness matter now become one of the main reasons by consumer in choosing smartphone. Therefore, this study analyzes how a perceived coolness of a product will be able to create a feeling of love for the brand itself. In this term, a coolness perception on a technology is seen as an important element and needs to be investigated further. This study uses six dimensions of brand love for technology product features, which are; attractiveness, difference, desire, usability, innovative technology, reliability coolness, and two other variables namely perceived coolness and brand love. Furthermore, a total of 236 valid data from respondents of all ages were collected for this study. The results show that four out of the six dimensions of brand love for technology product features have a positive impact on perceived coolness of a product, and the perceived coolness of a product has a positive impact on the brand love.